Economics of Arbitrability in International IP Contracting - dels Sants Mirambell Fargas, Miquel (Journal of Law and Commerce, 2019)
IP arbitrability in international commercial disputes enshrines the friction between traders and holders, between private contracts and public registers, between party autonomy and mandatory rules. Particularly, non‑arbitrability of invalidity defenses concerning registered industrial intellectual property rights has been insufficiently analyzed as a crucial matter of recognition and enforcement of international awards. Consequently, a sound economic rationale on grounds of competitive advantages is disregarded in too many instances. Having regarded the ever‑growing importance of IP rights for companies’ productivity and today’s primary use of arbitration in cross‑border contracting, the present research aims at pointing that out. It applies a transaction cost economics approach and takes into account the legal comparative background. The study finally examines arbitrability of IP validity with inter‑partes effect as an operable solution and the advantages of a predictable model as was early adopted by the United States.